Urgensi Aspek Penilaian dalam Evaluasi Pembelajaran - Marzuki, Ismail; Sholihah, Tuti; Imansyah, Faiz Atha (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
ABSTRACT In the world of education, a teacher must be able to distinguish students both in the ability of intelligence, mental, and personality. Because basically, all students are not the same. The ability of intelligence, mental and personality of each student has different levels there are low, medium and high. And to know that all teachers must understand what education evaluation is, but at this time not all teachers can apply the evaluation properly in education. The existence of educational evaluation is to produce value, this assessment has the aim to measure the success of learning as well as to measure the extent to which students are able to absorb the material that has been conveyed. While the assessment for teachers is to be feedback from the learning outcomes that have been conveyed. This research uses library research method research design, commonly known as library research.  Keywords: urgency, assessment, learning and evaluation